Plants, phytochemicals, and natural practices in complementary and alternative system of medicine for treatment of central nervous system disorders - Chinaza Godswill Awuchi (International Journal of Food Properties, 2023)
Complementary and alternative system of medicine has been at the center of drug discovery for different CNS disorders. Medicinal plants have been in use in healthcare settings and have interestingly fostered the leads for drug development aimed at treating various diseases such as CND disorders, malaria, mycetoma, and inflammation. Electroacupuncture (EA) has the ability to protect prolonged restraint stress, attenuate depressions, and manage few CNS disorders. Bacopa monnieri, Rhodiola rosea, Centella asiatica, Cannabis sativa, Curcuma longa, Cyperus rotundus, Morinda citrifolia, and Withania somnifera are among the most common plants used for treating CNS disorder. Bioactive compounds such as valtrate, curcumin, cannabinoids, apomorphine, pergolide, benzatropine, β-asarone, α-Asarone have been used to treat various CNS disorders, such as addiction, insomnia, depression, Alzheimer’s disease, epilepsy, vitiligo, Parkinson’s disease. These complementary and alternative system of medicines have promising lead in the quest to develop more drugs for CNS disorders.